OTOMATISASI TIRAI KAMAR BERBASIS AT89S51 - Yulianto, Arif Agus; Rahayu, Cicilia Puji; Nugroho, Budi (Siscode, 2013)
Design of curtain control system using AT89S51 microcontroller based light sensor is an idea that arises to meet the needs of the home automation system using the sensor as decision makers in the system. The problem is a system need something that can assist humans in performing activities for can be more efficient. To solve the above problems needed designed of a system that can be run automatically, in this case the system design based on microcontroller AT89S51 curtain with the help of light as a source of information. Design of curtain design automation tools using IC AT89S51 as the main controller, DC motor as curtain and assembly language as a programming language that has been loaded on the IC AT89S51. The workings of this tool design starts from the microcontroller to obtain information from the incoming light and the light received by the sensor to interrupt the action. In no light conditions, the sensor will work automatically closed curtain, and vice versa if the incoming light curtain will open automatically. Manufacturing automation tool based AT89S51 curtain can be run automatically with interrupts received by the microcontroller to open and close the curtains. However, using of a DC motor to drive rotation curtain less stable, for it is advisable for readers who want to develop this tool can use reducers to obtain a more stable rotation Keywords:Â AT89S51 Microcontroller, Assembly Language, Light Sensor, Curtain Room.